Bioconversion Of Isoflavones In Synbiotic-Soymilk Using Physical Treatments (Ultrasonication, Electroporation And Ultraviolet) On Lactobacilli And Bifidobacteria - Yeo , Siok Koon (2012)
Fifteen strains of lactobacilli and bifidobacteria were screened for growth in soymilk. L. casei FTDC 2113, L. acidophilus FTDC 8033, L. acidophilus BT 4356, L. casei BT 1268, Bifidobacterium sp. FTDC 8943 and B. longum FTDC 8643 exhibited higher (P<0.05) viability and were thus selected for subsequent analyses involving prebiotics such as fructooligosaccharides (FOS), inulin, mannitol, maltodextrin and pectin. All selected strains showed viability exceeding 7 Log10 CFU/mL upon fermentation in soymilk at 37 oC for 24 h and was higher upon supplementation with maltodextrin, mannitol and FOS.